2010
DOI: 10.1590/s2179-975x2010000200004
|View full text |Cite
|
Sign up to set email alerts
|

Richness and distribution of aquatic macrophytes in Brazilian semi-arid aquatic ecosystems

Abstract: Aim: The aim of this study was to evaluate the richness and distribution of the aquatic macrophytes in the basin of the Apodi/Mossoró River, in the semi-arid region (caatinga) of Rio Grande do Norte, Brazil; Methods: A survey of the floristic composition of the aquatic macrophytes was made at 20 sampling stations in the basin at four seasons (August/2007, November/2007, February/2008, May/2008. Specimens of each species were collected and deposited in the Dárdano de Andrade Lima Herbarium of the Universidade F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
15

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 10 publications
2
8
0
15
Order By: Relevance
“…The representativeness of families occurring in a study area can also be impaired by urbanization. Poaceae had good representation in our study, as it did in the study of Carvalho et al (2005), which evaluated the level of macrophyte infestation on the Tiete River and recorded five species (33.3% of the total), and also in the study of Henry-Silva et al (2010), which identified five species (11.36% of the total) of this family in river ecosystems of the Brazilian semi-arid region.…”
Section: Discussionsupporting
confidence: 63%
“…The representativeness of families occurring in a study area can also be impaired by urbanization. Poaceae had good representation in our study, as it did in the study of Carvalho et al (2005), which evaluated the level of macrophyte infestation on the Tiete River and recorded five species (33.3% of the total), and also in the study of Henry-Silva et al (2010), which identified five species (11.36% of the total) of this family in river ecosystems of the Brazilian semi-arid region.…”
Section: Discussionsupporting
confidence: 63%
“…The other works that include species of Cyperus occurring in the state are only lists (Almeida Júnior & Zickel 2009;Henry-Silva et al 2010;Oliveira et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…All aquatic macrophytes recorded in Ourinhos Reservoir are common in Neotropical reservoirs and lakes (Vilarrubia and Cova, 1993;Bini et al, 1999Bini et al, , 2005Neiff, 2001;Nahlik and Mitsch, 2006;Neiff et al, 2008;Martins et al, 2008;Bianchini Junior et al, 2010;Henry-Silva et al, 2010;Piedade et al, 2010;Rolon et al, 2010;Alves Ferreira et al, 2011). In the Paranapanema watershed, these species were also usually recorded in the following reservoirs: Rosana, Salto Grande, Chavantes, Piraju and Jurumirim (Henry and Nogueira, 1999;Casatti et al, 2003;Martins et al, 2008;Neves, 2008;Bianchini Junior and Cunha-Santino, 2014).…”
Section: Discussionmentioning
confidence: 99%